Efecto de los Parámetros de síntesis en la Estabilidad de Nanopartículas Bimetálicas basadas en Oro Sintetizadas por Ruta Química - Asmat Campos, David Angel (2012)
In this research work has been synthesized and characterized by chemical route monometallic and bimetallic nanoparticles Core / Shell (Au / Ag), using two-step method involving the preparation of a solution of nuclei formed by gold nanospheres and its union with the armor formed by silver nanospheres; to this, the final size of the nanostructure, intimately dependent kernel size for that matter studied and experimentally examined the influence of parameter variation in the synthesis process._x000D_ It basically studied the influence of synthesis parameters on the gold nucleus, then it choose the best conditions and make the coating and produce silver bimetallic nanostructures. Variations were such as: Method of synthesis of the nanosphere, temperature stabilizing cetyltrimethylammonium bromide (CTAB) 65, 75, 85 and 95 °C, precursor Origin of chloroauric acid (HAuCl4) Stabilizer Type homogenization CTAB (agitation ultrasonic and magnetic stirring), temperature and dwell time of the reducing solution of sodium borohydride (NaBH4), Homogenization of reactants end. Likewise synthesize nanospheres was achieved Silver, which would become the coating (shell), the results showed good spectrophotometrically synthesis, indicating a peak at 422 nm plasmonic typical of this type of nanostructure for silver._x000D_ The understanding and control of the different experimental parameters during synthesis, are the key to a successful production of Au nanospheres. Patterns of X-ray diffraction (XRD) showed peaks (111), (200) and (220) characteristic of the structure of the gold. The optical absorbance spectra show peaks within the range of 528 to 537 nm, typical gold nanospheres, whose intensities are increased in function of the variables described in this work. Analysis by Dynamic Light Scattering (Dynamic Light Scattering - DLS) in colloidal solutions showed less polydisperse and nanosized when stabilized with CTAB dissolved at 95 ° C. These results were compared with TEM images